Low duty cycle and low collision asynchronous MAC protocol for wireless sensor network - Zhe-tao LI; Geng-ming ZHU; Zhi-qiang WANG; Ting-rui PEI; Gao-feng PAN (Tongxin xuebao)
Improving the quality of channel listening is an effective way to reduce energy consumption and improve communication efficiency.PB-MAC(predict-base MAC),a novel low duty cycle and low collision asynchronous MAC protocol was presented.PB-MAC lowers sensor duty cycle by enabling senders to predict receiver wakeup times.An ef-ficient prediction-based reconnection and retransmission mechanism was introduced to achieve low collisions and high efficiency retransmission.Comparison of PB-MAC on OMNet++ with RI-MAC and X-MAC was evaluated.Evaluated on scenarios with 50 random disposed nodes,the average duty cycle,consumed energy and average collisions for PB-MAC is 68.60%,24.75% and 68.05% less than those of RI-MAC and 64.39%,64.05% and 70.54% less than those of X-MAC respectively.In grid network,PB-MAC also outperforms RI-MAC and X-MAC protocols.